Using a hybrid multi-criteria analysis method to classify hot mix asphalt regarding permanent deformation - Victória Nunes-Ramos; Jéssica da Silva Vieira; Alejandro Ruiz-Padillo; Luciano Pivoto Specht (Transportes)
The new Brazilian pavement design method (MeDiNa) defines the Flow Number as an indicator of permanent deformation of asphalt mixtures, which is adapted to traffic by trial and error, as there is no established combination of parameters in the literature for its prediction. In this sense, multi-criteria decision-making support methodologies can help optimize the mix composition process by simultaneously combining simplified indicators. Therefore, this study used a hybrid multi-criteria method (SMART and TOPSIS) to classify asphalt mixtures by combining parameters obtained in the design of these materials, comparing them with the ranking found by Flow Number. Based on the relative importance assigned by a panel of experts, it was found that it is possible to obtain a ranking statistically similar to that of Flow Number using only data from softening point and viscosity of the binder, granulometric range, shape index of the aggregate fraction #3/4 and binder content. The method is more effective for traffic of less than 6.8E+07 repetitions of standard axis under normal conditions. Therefore, the research has shown that it is feasible to simplify the design of mixtures for surfacing flexible pavements by filtering out the mixtures sent for more laborious tests such as Flow Number, limiting the number of tests to only the best-placed test mixtures. It also makes it possible to rationalize the design of low-traffic roads where there are no resources to carry out the test proposed by MeDiNa, helping designers to make decisions based on simplified indicators.